77.4k views
2 votes
What is the solution to 7-5x=-5x-6x+7

2 Answers

5 votes

7-5X=-5X-6x7

Delete equal terms on both sides of the equation

7=-6x7

multiply the numbers

7=-42

the proportion is false for any value of X

What is the solution to 7-5x=-5x-6x+7-example-1
User Mamiko
by
5.1k points
4 votes

7-5x=-11x+7

7+6x=7

6x=0

x=0

0 is the solution to x

User Artsiom Miklushou
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.